Molecular evolution of the vertebrate blood coagulation network - Davidson, Colin J.; Hirt, Robert P.; Lal, Kalpana; Snell, Philip; Elgar, Greg; Tuddenham, Edward G. D.; McVey, John H. (Thrombosis and Haemostasis, 2003)
In mammalian blood coagulation 5 proteases, factor VII (FVII), factor IX (FIX), factor X (FX), protein C (PC) and prothrombin act with two cofactors factor V and factor VIII to control the generation of fibrin. Biochemical evidence and molecular cloning data have previously indicated that blood coagulation involving tissue factor, prothrombin and fibrinogen is present in all vertebrates. Using degenerate RT-PCR we have isolated and characterized novel cDNAs with sequence identity to the blood coagulation serine proteases and cofactors from chicken and the puffer fish (Fugu rubripes). Sequence alignments, phylogenetic and comparative sequence analysis all support the existence of the Gla-EGF1-EGF2-SP domain serine proteases FVII, FIX, FX, PC and the A1-A2-B-A3-C1-C2 domain protein cofactors FV and FVIII in these species. These results strongly suggest that the blood coagulation network is present in all jawed vertebrates and evolved before the divergence of tetrapods and teleosts over 430 million years ago; and that vertebrate blood coagulation may have benefited from two rounds of gene or whole genome duplication. Sequences identified in Fugu coding for additional FVII-like, FIX-like and PC-like sequences support the possibility of further tandem and large-scale duplications in teleosts. Comparative sequence analyses of amino acid residues in the active site region suggest these additional sequences have evolved new and as yet unknown functions.Supplementary information to this article available at both http://europium.csc.mrc.ac.uk and www.thrombosis-online.com
Keywords: Evolution; serine proteases; blood coagulation; cofactors